Can Bugis-Makassar Local Culture Reduce Compulsive Buying Behavior? - Kasnaeny Karim; Ibrahim Dani (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2022)
This study aims to determine whether the local wisdom of Bugis culture is able to minimize consumer behavior in purchasing products, considering the negative impact caused by excessive shopping behavior with the use of credit cards that exceed the limit of funds or without the use of credit cards. Research informants amounted to 100 people obtained through snowball sampling. Research data were collected through open and closed questionnaires and interviews, then the research instrument was tested through validity and reliability tests using triangulation and peer review methods. The research method uses a narrative qualitative approach to obtain an explanation of whether the local wisdom of Bugis culture, namely